John Skelton : the critical heritage - Edwards, A. S. G. (Anthony Stockwell Garfield), 1942- (Critical heritage series., 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling student and researcher to read the material themselves.